Research perspectives on the photocatalytic activity of titanium dioxide: Catalytic assessment methods in solution and solid-state in relation to particle surface activity. (August 2021) - Allen, Norman S.; Edge, Michele; Sandoval, Gonzalo; Verran, Jo; Catalina, Fernando; Bygott, Claire; Kerrod, Julie
Highlights: A range of pigmentary and nano particle titanium dioxides have been characterised by Brunauer-Emmett-Teller (BET) surface area, X-ray Diffraction (XRD), CPS Disc Centrifuge, Transmission Electron Microscope (TEM), Scanning Electron Micrographs (SEM), Thermogravimetric Analysis (TGA) and Fourier Transform Infrared Measurements (DRIFTS). Photoactivities were determined by a wide range of test methods based on Microwave Dielectric Spectroscopy (MDS), Hydroxyl content, Phosphorescence and Chemiluminescence Spectroscopy and Isopropanol Oxidation/oxygen adsorption. Quantum size effects, which lead to high surface areas and blue shifts and diminish electron–hole recombination, are used to explain the high activities of the nanoparticle products. Light exposure studies on doped metallocene polyethylene films have been undertaken in dry/humid conditions and the data related to the analysis and test methodologies. Abstract: A range of prepared titania nanoparticles were characterised by Brunauer-Emmett-Teller (BET) surface area, X-ray Diffraction (XRD), CPS Disc Centrifuge, Transmission Electron Microscope (TEM), Scanning Electron Micrographs (SEM), Thermogravimetric Analysis (TGA) and Fourier Transform Infrared Measurements (DRIFTS). In addition, the activities of the different catalysts were determined via rapid assessment methodologies like Microwave Dielectric Spectroscopy (MDS), Hydroxyl content, Phosphorescence and Chemiluminescence Spectroscopy and Isopropanol Oxidation Test and the data related to actual weathering properties of the pigments doped in metallocene polyethylene under dry and humid conditions. Quantum size effects, which lead to high surface areas and blue shifts and diminish electron–hole recombination, are used to explain the high activities of the nanoparticle products. In situ FTIR data and OH content determination show the presence of high contents of hydroxyl groups and large amounts of adsorbed water on TiO2 nanoparticles. The Disc Centrifuge results and BET surface area combined with the XRD particle size results show that a careful distinction between the crystal and aggregate sizes must be made in order to properly interpret the activity of TiO2 pigments. Aggregation of TiO2 pigments affects not only the surface area offered by the TiO2 but also the type of interaction between the light and the TiO2 . The treatment conditions used for the crystallization of the primary material (precursor) in order to prepare the nanoparticle pigments, not only influenced the anatase crystal size but also other anatase properties (such as the surface hydroxylation, adsorbed water, recombination rate, aggregation state and type of structural defects). Chemiluminescence of the titania particles is discussed in light of potential surface active peroxidic species.